The Analysis of The Impact of Accounting Information System on The Effectiveness of Internal Control - Mas Said Resna Hadiwijaya; Agung Praptapa; Icuk Rangga Bawono (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2020)
The phenomenon of low effectiveness of internal PT. Langen Kridha Pratyangga Sumedang was presumed to form the reflection of low in accounting information system components. This presumption must be proved and seeked its truth and solution because of the accounting information system components give indication that organization was managed with good and fundamentally will produce the effective employee’s behavior in achieving organization goals. This research takes the title: The Analysis of The Impact of Accounting Information System on the Effectiveness of Internal Control (Case Study at PT. Langen Kridha Pratyangga Sumedang). The research used to approach was theory of reasoned action which explains organizational behavior in a system. The implementation of this research used quantitative method, by using purposive sampling technique. The sample size was 70 persons of employees which were distributed equally to employee whose listed as employee at PT. Langen Kridha Pratyangga and have passed 3 months trial. Questionnaire and interview are used as research technique and multiple linear regression was used as the method of analysis. The result of this research at PT. Langen Kridha Pratyangga Sumedang indicated that (1) the people/human resources have no influence on the effectiveness of internal control, (2) the procedures and instructions have significant and positive influence on the effectiveness of internal control, (3) the data have significant and positive influence on the effectiveness of internal control, (4) the software has significant and positive influence on the effectiveness of internal control, (5) information technology infrastructure has significant and positive influence on the effectiveness of internal control. The result of this research gives implication in taking policy to increase internal control effectiveness. So, The Director of PT. Langen Kridha Pratyangga Sumedang and institution that related with others have expected to pay attention on people/human resources, procedure and instruction, data, software, and technology information infrastructure because four of these variables have significant and positive influence on the internal control.